HUBUNGAN AKTIVITAS MELIPAT KERTAS DENGAN PERKEMBANGAN MOTORIK HALUS ANAK DI TAMAN KANAK-KANAK ISLAM TERPADU RABBANI BATAM TAHUN 2021 - Rini Susanti; Rusdani Rusdani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Children cannot separate between playing and learning. For children, playing is all children's activities including learning, fun, and is a method of how they get to know the world. One of the play activities is paper folding activity. Paper folding activity is a fun activity and can help children in increasing creativity, imagination, perseverance and accuracy. This can help children improve fine motor development to be more optimal, because children can use hand-eye coordination to produce good folds and increase their creativity. Method: Cross sectional. The research was conducted at the Rabbani Integrated Islamic Kindergarten in Batam. The sampling technique was total sampling with a sample of 40 children. Data collection used checklist sheets and DDST II sheets. Data analysis using Chi-square. Results: There were 16 children whose paper folding activities had not yet developed, so 10 (62.5%) children had fine motor development that was not in accordance with their developmental age and 6 (37.5%) children were in accordance with their developmental age. There were 24 children developing paper folding activities, so that 21 (87.5%) children had fine motor development according to their developmental age and 3 (12.5%) children did not. Based on statistical tests, paper folding activity with fine motor development obtained p value = 0.003. Conclusion: Based on the results of this study, it can be concluded that there is a relationship between paper folding activities and children's fine motor development at the Rabbani Batam Integrated Islamic Kindergarten in 2021.Keywords: Folding Paper, Fine Motor, Children.